A literature review of the reentry and adjustment experience of college students returning from short-term international christian mission experiences and implications for student affairs professionals - Weber, Wade Michael (Kansas State University, 2009)
With increased attention related to internationalization and intercultural learning within higher education, increasing numbers of college students are participating in international cross-cultural activities. Participants in short-term international Christian mission experiences are increasing dramatically. These students frequently participate in such activities during the course of their college career and subsequently experience reentry issues during their readjustment back into college life. This report reviews literature and student comments related to the reentry experiences of the growing college population of short-term international Christian mission participants. What follows is a review of various explanations of the reentry phenomenon related to socio-psychological, expectation, systems, identity formation, and grief theories. College adjustment and support literature, as it relates to student retention, is explored along with reentry services and practices associated with student affairs, international program offices, and collegiate Christian campus ministries or colleges. Student affairs professionals have a strategic role to play by intervening with students returning from short-term international experiences. By providing personal and programmatic support for students readjusting to American culture, we have the opportunity to assist students integrate what they have learned from their global experience into the development of individual identities, values, and behaviors. There are substantive educational, spiritual, social, and psychological reasons given from the literature to justify a level of intervention, unique and appropriate for each individual institution, from student life professionals directed towards supporting college students as they return from short-term international Christian mission experiences. This review highlights the need for more extensive in depth studies seeking to understand the relationship between interpersonal and programmatic support and the learning process of college students as they go through the reentry experience.
Keywords: Reentry; Christian Mission; Adjustment; Student Affairs; International Experiences; College Students; Education, Guidance and Counseling (0519); Education, Higher (0745); Psychology, Cognitive (0633)